Structure and dynamics of liquid methanol confined within functionalized silica nanopores - Elola, M.D. (2010)
Molecular dynamics simulations have been carried out to investigate the structure and dynamics of liquid methanol confined in 3.3 nm diameter cylindrical silica pores. Three cavities differing in the characteristics of the functional groups at their walls have been examined: (i) smooth hydrophobic pores in which dispersive forces prevail, (ii) hydrophilic cavities with surfaces covered by polar silanol groups, and (iii) a much more rugged pore in which 60% of the previous interfacial hydroxyl groups were replaced by the bulkier trimethylsilyl ones. Confinement promotes a considerable structure at the vicinity of the pore walls which is enhanced in the case of hydroxylated surfaces. Moreover, in the presence of the trimethylsilyl groups, the propagation of this interface-induced spatial ordering extends down to the central region of the pore. Concerning the dynamical modes, we observed an overall slowdown in both the translational and rotational motions. An analysis of these mobilities from a local perspective shows that the largest retardations operate at the vicinity of the interfaces. The gross features of the rotational dynamics were analyzed in terms of contributions arising from bulk and surface states. Compared to the bulk dynamical behavior, the characteristic timescales associated with the rotational motions show the most dramatic increments. A dynamical analysis of hydrogen bond formation and breaking processes is also included. © 2010 American Institute of Physics.